HAKIKAT DAN PROSES PENDIDIKAN LINTAS PERSPEKTIF (Tradisionalisme, Modernisme, Dan Postmodernisme) - Suhendra, Ade (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
The purpose of this study is to describe the nature and process of education across perspectives: traditionalism, modernism, and postmodernism. The study is conducted by reviewing the related literature, later is identified by the points referred. Based on this study is concluded that each perspective has a foundation of each appropriate to the context and circumstances in which it is built. Perspective traditionalism built in the context and circumstances in which the teacher becomes the dominant component. Meanwhile, in the perspective of modernism, assumes that the educational process that goes with changing ideologies, customs, institutions long time and so forth, so that it becomes to be in accordance with the opinions and new circumstances bring about science and modern technologies. The views postmodernism emphasizes individualism assumes that each individual has a different meaning, so this brings consequences in the world of education, so that the implications for the educational process is the presence of relativity. Hence the assumption of traditionalism could be used, as well as modernism. Although in essence, postmodernism cannot be said as well of traditionalism or modernism.Â